Will it Last? An Assessment of the 2001 German Pension Reform - Holger Bonin (Institute for the Study of Labor (IZA), 2001)
In May 2001, Germany adopted a fundamental pension reform cutting back public pensions and introducing personal pension accounts. The paper critically reviews the reform decisions and evaluates their long-term viability. It is shown that the adjustment of the Public Pension Scheme misses the proclaimed contribution rate and replacement ratio targets already under moderate economic conditions. However, the new private pension plans provide scope for further downsizing state pensions, necessary beyond 2025. As the enacted savings rate target is conservative, individual pensions keep retirement income sufficient even if returns to pension funds are low due to legal restrictions on savings vehicles.
Keywords: F22; E66; 330; Pension reform; pension funding; fiscal projections; Germany; Gesetzliche Rentenversicherung; Rentenreform; Wirtschaftspolitische Wirkungsanalyse; Alterssicherung; Sozialversicherungsbeitrag; Sparen; Rendite; Prognose; Deutschland